Research on Optimal Shift Control Strategy of Two-speed AMT based on Fuzzy Control. (June 2020) - Ma, Ning; Hou, Benjiang; Wang, Yexuan; Ren, Kai; Chen, Shaoxin; Wang, Peng; Lin, Rongfeng; Ji, Jianyi; Ji, Yichun; Han, Zhendong; Yang, Chaohui; Wang, Lingmin; et al.
Abstract: For a two-speed AMT pure electric commercial vehicle, the pros and cons of the shift control strategy directly determine the overall vehicle performance of the electric vehicle, such as power and economy. This article takes a certain type of commercial pure electric vehicle equipped with a two-speed automatic transmission as the research object, formulates a dynamic shift rule based on the torque map of the motor, structures an economic shift rule based on the efficiency map, and identifies road gradient and Car load quality, comprehensive consideration of the car's loading quality, road slope, accelerator pedal opening, accelerator pedal opening change rate, vehicle speed and other parameters for optimal shift control strategy formulation. Comparing the dynamic shift strategy with the economic shift strategy, simulation analysis results show that the optimized shift control strategy can meet the requirements of dynamic performance and has the advantages of economy and energy saving.